PEMETAAN DAERAH RAWAN LONGSOR DI WILAYAH SUB DAS TONDANO DENGAN SISTEM INFORMASI GEOGRAFIS - Melisa P. Todingan; Meldi Sinolungan; Yani E.B. Kamagi; Jeanne Lengkong (COCOS, 2014)
ABSTRACTThe purpose of this study was to analyze the landslide prone areas in Sub Watershed of Tondano in order to obtain the vulnerability information and dissemination in the form of map by using the Geographic Information Systems. The study was conducted by using a Descriptive Method which consisted of a survey and map overlay, while the identification of areas prone to landslides using the scoring method. Parameters measured were soil type , slope , elevation , land use and rainfall . The results showed that the spread of landslide-prone areas in the Sub Watershed of Tondano consisted of five classes of landslide susceptibility, namely (1) No class landslide prone area of 993.12 ha, or 23.64%, spread over an area of 137.42 ha districts Eris, Kakas of 1.31 ha and 854.39 ha area of East Tondano; (2) The low vulnerability class area of 207.59 ha, or 4.94%, spread over an area of 144.10 ha district of Eris, Kakas area of 0.29 ha and 63.20 ha area of East Tondano; (3) Moderate impact class area of 894.19 ha, or 21.28% spread over an area of 503.06 ha district of Eris, Kakas area of 114.97 ha and 276.16 ha area of East Tondano; (4) High vulnerability class area of 469.23 ha, or 11.17% spread over an area of 256.27 ha district of Eris, Kakas area of 48.03 ha and 164.93 ha area of East Tondano; (5) Highest area of 1637.23 ha or 38.97% spread over area of 455.60 ha district of Eris, Kakas area of 45.46 ha and 1136.17 ha area of East Tondano.Key Words : Mapping, Landslide, Sub Watershed of Tondano, GIS (Geographic Information System)